Washington State Women's Building, with the Alaska Building on left, Alaska Yukon Pacific Exposition, Seattle, 1909. - Nowell, Frank H., 1864-1950 (1909)
Exterior view and grounds PH Coll 727.626 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number